Morbidity and mortality in adult-onset IgA vasculitis: a long-term population-based cohort study. (29th March 2021) - Nossent, Johannes; Raymond, Warren; Isobel Keen, Helen; Preen, David; Inderjeeth, Charles
Abstract: Objectives: With sparse data available, we investigated mortality and risk factors in adults with IgA vasculitis (IgAV). Methods: This was an observational population-based cohort study using state-wide linked longitudinal health data for hospitalized adults with IgAV ( n  = 267) and matched comparators ( n  = 1080) between 1980 and 2015. Charlson comorbidity index (CCI) and serious infections (SIs) were recorded over an extensive lookback period prior to diagnosis. Date and causes of death were extracted from the Western Australia Death Registry. Mortality rate (deaths/1000 person-years) ratios (MRRs) and hazard ratio (HR) for survival were assessed. Results: During 9.9 (9.8) years lookback patients with IgAV accrued higher CCI scores (2.60 vs 1.50, P  < 0.001) and had higher risk of SI (OR = 8.4, P  < 0.001), not fully explained by CCI scores. During 19 years' follow-up, the rate of death in patients with IgAV ( n  = 137) was higher than in comparators ( n  = 397) (MRR = 2.06, 95% CI: 1.70–2.50; P  < 0.01) and the general population (standardized mortality rate ratio = 5.64, 95% CI: 4.25, 7.53; P  < 0.001). Survival in IgAV was reduced at 5 (72.7 vs 89.7%) and 20 years (45.2% vs 65.6%) (both P  < 0.05). CCI (HR = 1.88, 95% CI: 1.25, 2.73; P  = 0.001), renal failure (HR = 1.48, 95% CI: 1.04, 2.22; P  = 0.03) and prior SI (HR = 1.48, 95% CI: 1.01, 2.16; P  = 0.04) were independent risk factors. Death from infections (5.8 vs 1.8%, P  = 0.02) was significantly more frequent in patients with IgAV. Conclusion: Premorbid comorbidity accrual appears increased in hospitalized patients with IgAV and predicts premature death. As comorbidity does not fully explain the increased risk of premorbid infections or the increased mortality due to infections in IgAV, prospective studies are needed.